Methods of deference in human rights adjudication - Chan, S (2022)
The phenomenon of judicial deference to the executive or legislature in human rights adjudication has elicited extensive scholarly discussions. Whilst much has been written on whether and when courts should defer, this thesis is the first to systematically probe two questions regarding how courts should defer.